2020
DOI: 10.1016/j.mcn.2019.103463
|View full text |Cite
|
Sign up to set email alerts
|

Δ9-tetrahydrocannabinol and 2-AG decreases neurite outgrowth and differentially affects ERK1/2 and Akt signaling in hiPSC-derived cortical neurons

Abstract: 9 -tetrahydrocannabinol and 2-AG decreases neurite outgrowth and differentially affects ERK1/2 and Akt signaling in hiPSC-derived cortical neurons. Molecular and Cellular Neuroscience, 103, [103463].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…To investigate this, we used hiPSC-NPCs from three typically developing male individuals with no history of psychiatric illness [M1, M2, and M3; table S1 and fig. S1; ( 27 , 28 )] and treated these cells with IFN-γ (25 ng/ml) daily on days (D) 17 to 21 of differentiation. Subsequently, IFN-γ was excluded from cell culture media, and neuronal differentiation was continued, resulting in post-mitotic hiPSC neurons ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate this, we used hiPSC-NPCs from three typically developing male individuals with no history of psychiatric illness [M1, M2, and M3; table S1 and fig. S1; ( 27 , 28 )] and treated these cells with IFN-γ (25 ng/ml) daily on days (D) 17 to 21 of differentiation. Subsequently, IFN-γ was excluded from cell culture media, and neuronal differentiation was continued, resulting in post-mitotic hiPSC neurons ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two ASD lines were generated using CytoTune Sendai reprogramming kits (Thermo Fisher Scientific, A16517). HiPSC reprogramming was validated as previously described ( 24 , 27 , 28 , 56 ). Briefly, genome-wide expression profiling using Illumina BeadChip v4 and the bioinformatics tool “Pluritest” was used to confirm hiPSC identity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results provide a mechanism where FAK and MAPK integrate signals from CB 1 , integrins, and RTKs. CB 1 signaling through FAK and MAPK may play important physiological roles in CB 1 regulation of the actin cytoskeleton, neuronal migration, proliferation, and generation of neuritic processes (Harkany et al, 2008;Zorina et al, 2010;Jung et al, 2011;Peng and Guan, 2011;Gaffuri et al, 2012;Roskoski, 2012;Shum et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that CB 1 regulates ERK1/2 phosphorylation/activation via several mechanisms that include G i/o protein activation (Galve-Roperh et al, 2002;Davis et al, 2003;Dalton and Howlett, 2012), RTK transactivation (Dalton and Howlett, 2012), and Src activation (Derkinderen et al, 2003;Dalton and Howlett, 2012) under various stimuli and conditions. Given the importance of FAK and ERK1/2 in the endocannabinoid system's role in neuronal migration and neuritogenesis, it is important to determine whether CB 1 -mediated FAK 925 Tyr-P is required for efficient ERK1/2 pathway activation in neuronal focal adhesions (Cox et al, 2006;Harkany et al, 2008;Samuels et al, 2009;Zorina et al, 2010;Shum et al, 2020).…”
Section: Introductionmentioning
confidence: 99%